2015
DOI: 10.1159/000381259
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of High-Sensitive Troponin I in Stable Coronary Artery Disease Depends on Age and Other Clinical Variables

Abstract: Objectives: To study the prognostic value of high-sensitive troponin (hs-cTn) I in stable coronary artery disease. Methods: In total, we studied 705 patients. Secondary outcomes were the incidence of: (1) acute ischemic events and (2) heart failure or death. The primary outcome was the composite of them. Results: Patients with hs-cTnI >0 ng/ml (62.1%) were older, had a lower estimated glomerular filtration rate, more frequent a history of hypertension, atrial fibrillation, ejection fraction <40%, and therapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…However, high-sensitivity cardiac troponin assays have also shown promise as prognostic biomarkers of cardiovascular risk in a variety of ambulatory outpatient settings, including among those with known vascular disease,[28, 29] the elderly [30, 31] and in general population-based studies. [27, 3235] The cause of chronic, low-level troponin elevation in these populations is uncertain, although speculated mechanisms include subclinical ischaemia, microvascular dysfunction or apoptosis of myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, high-sensitivity cardiac troponin assays have also shown promise as prognostic biomarkers of cardiovascular risk in a variety of ambulatory outpatient settings, including among those with known vascular disease,[28, 29] the elderly [30, 31] and in general population-based studies. [27, 3235] The cause of chronic, low-level troponin elevation in these populations is uncertain, although speculated mechanisms include subclinical ischaemia, microvascular dysfunction or apoptosis of myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that in older patients, who already have a higher prevalence of structural cardiac abnormalities (ie, stage B HF) and subclinical atherosclerosis, the role of vitamin D relative to other traditional risk factors is less impactful. Elevated hs‐cTnT is more common in older adults because of a higher prevalence of nonacute coronary syndrome conditions like structural heart disease . A level of 14 ng/L is also a much more extreme elevation by percentile of population in a younger person than in an older person.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, for patients with acute coronary syndromes, a prior study found that the relative prognostic significance of an elevated troponin level attenuates with age, such that an elevated troponin value confers a higher relative risk among younger compared with older adults . Furthermore, the diagnostic performance of hs‐cTnT for acute coronary syndromes is superior in younger versus older adults …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations